The Correlation between knowledge and self-efficacy in preventing the spread of Pulmonary Tuberculosis - Bisepta Prayogi (Journal of Ners and Midwifery, 2017)
The World Health Organization (WHO) has stated that the current situation of Tuberculosis (TB) worldwide is getting worse. Based on the survey conducted by the Ministry of Health of the Republic of Indonesia (2011) on the prevalence of TB in 2009, knowledge shows that 76% of families have heard about TB and 85% know that TB can be cured, but only 26% can mention two signs and symptoms main TB. The mode of transmission of TB is understood by 51% of families and only 19% know that TB drugs are available for free. The purpose of this research is to know the relationship between knowledge and self-efficacy about prevention of transmission in lung tuberculosis patients. Methods: The research design used was correlational with the cross-sectional approach. The population is lung TB patients in the working area of Ponggok Puskesmas. Sampling technique using purposive sampling with a sample of 20 respondents. The data collected was then processed and analyzed using spearman-rho statistic test with a significance value of 0.05. Results: The results showed significance value p = 0,001 (p <0,05). Thus there is a relationship between knowledge and self-efficacy about prevention of transmission of pulmonary tuberculosis. Discussion: Knowledge is one factor that plays a role in the formation of self-efficacy in patients with pulmonary tuberculosis.